2019
DOI: 10.1002/ece3.5014
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeographic patterns and conservation implications of the endangered Chinese giant salamander

Abstract: Understanding genetic diversity patterns of endangered species is an important premise for biodiversity conservation. The critically endangered salamander Andrias davidianus , endemic to central and southern mainland in China, has suffered from sharp range and population size declines over the past three decades. However, the levels and patterns of genetic diversity of A. davidianus populations in wild remain poorly understood. Herein, we explore the levels and phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 46 publications
(80 reference statements)
1
19
0
Order By: Relevance
“…A further caveat in model interpretation could be clade‐specific variability and phenotypic plasticity. Yan et al () and Liang et al () uncovered seven divergent mitochondrial clades in A. davidianus . Besides, Riddell, Odom, Damm, and Sears () revealed that plasticity may contribute in buffering salamander species from climate change.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A further caveat in model interpretation could be clade‐specific variability and phenotypic plasticity. Yan et al () and Liang et al () uncovered seven divergent mitochondrial clades in A. davidianus . Besides, Riddell, Odom, Damm, and Sears () revealed that plasticity may contribute in buffering salamander species from climate change.…”
Section: Discussionmentioning
confidence: 99%
“…While the effects of climate change are largely studied in surface habitats, the impacts on subterranean habitats are still poorly explored (Mammola, Cardoso, et al, ; Mammola, Piano, et al, ). Andrias davidianus primarily exploits habitats at the surface/subterranean interface for breeding (Liang et al, ; Luo et al, ). The temperature increment in these transitional subterranean habitats is expected to parallel the external one almost synchronically (Mammola, Piano, et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations